PARENT CARE RELATIONSHIP WITH RESULTS STUDENT LEARNING AT SD NEGERI 1 KAYU AGUNG DURING THE COVID-19 - Yun Ratna Lagandesa; Iksan Iswandi (Universitas Tadulako, 2021)
The problem examined in this study is the concern of parents with student learning outcomes at SD Negeri 1 Kayu Agung. The purpose of this study was to see the relationship between parental attention and student learning outcomes at SD Negeri 1 Kayu Agung during the covid-19 period. The data analysis technique is using inferential statistical analysis, namely the technique of analyzing the calculation of products from people using a rough number formula. Based on the results of research and data analysis that has been conducted by researchers, it is shown that there is a significant relationship between parental attention and student learning outcomes at SD Negeri 1 Kayu Agung. This can be seen based on the calculation results obtained that the value of rcount> rtabel at a significant level of 5% or 0.05, namely 0.488> 0.344, which means that there is a relationship between parental attention and learning outcomes of SD Negeri 1 Kayu Agung students or the proposed hypothesis is accepted in the results. The calculation and interpretation of the level of the relationship between the coefficient values can be considered sufficient that there is a strong positive relationship between parental attention and student learning outcomes at SD Negeri 1 Kayu Agung based on the calculation results are at 0.400-0.599.